ANALISIS PENGEMBANGAN INDUSTRI KECIL MAKANAN RINGAN (Studi Kasus Industri Keripik Pisang di Kabupaten Merangin) - Yulinanda, Yulinanda (e-Journal Perdagangan Industri dan Moneter, 2013)
This research intent to know condition of industrial entrepreneur economy social little alimentary demulcent (banana flaky industry), factor that regard alimentary little industry development demulcent (banana flaky industry) and little industrial development prospect alimentary demulcent (banana flaky industry) at Merangin Regency. Result observationally to point out that entrepreneurs aged average industrial little alimentary demulcent (banana flaky industry) are surrounding 36-55 years, and on a par entrepreneur education zoom banana flaky which is end SMA, with family responsibility amount as much 3-4 person, averagely increases alimentary industrial entrepreneur capital demulcent (banana flaky industry) as big as Rp.2.196.777,- and with income average which gotten by banana flaky entrepreneur as big as RP.11.382.422,- every years. Factor that regards significant's ala little industry development at Regency Merangin which is capital, labour, and raw material. Where is construction frequency variable not significant's ascendant to production volume. Based on SWOT analysis, alimentary little industry demulcent (banana flaky industry) at Merangin's Regency have good development prospect to be developed. Keywords: Industry, SWOT. REFERENCES Anonim, 2009, Indikator Industri Kota Jambi, Badan Pusat Statistik Kota Jambi. Anonim, 2009, Indikator Industri Kabupaten Merangin, Badan Pusat Statistik Kabupaten Merangin. Anonim, 2009, Laporan Tahunan, Dinas Perindustrian dan Perdagangan Kota Jambi. Anonim, 2009, Laporan Tahunan, Dinas Perindustrian dan Perdagangan Kabupaten Merangin. Badriwan, Zaki, 1992, Intermediate accounting, BPFE-UGM, Yogyakarta. Azhari, SI, 1986. Industri Kecil Sebuah Tinjauan dan Perdagangan, LP3ES. Jakarta. Dumairy, 1997, Perekonomian Indonesia, Erlangga, Jakarta. Gilarso, T, 1992, Pengantar Ilmu Ekonomi, BPFE, Yogyakarta Harlik,H.; Amri,A.;Hardiani,H.(2013). Faktor-Faktor yang Mempengaruhi Kemiskinan dan Pengangguran di Kota Jambi. Jurnal Perspektif Pembiayaan dan Pembangunan Daerah. 1(2), 109-120Hardiani,H.(2011). Pendekatan Upah Bayangan (Shadow Wage) Untuk Estimasi Penawaran Tenaga Kerja Usaha Tani Kecil (Kasus Perkebunan Karet Rakyat di Kabupaten Muaro Jambi Provinsi Jambi. Jurnal Paradigma Ekonomika. 1(4)Tan, Syamsurijal, 2009. Perencanaan Ekonomi : Theori dan Implementasinya. Winardi, 1997, Pengantar Ilmu Ekonomi, Tarsiti, Bandung.